2019
DOI: 10.31557/apjcp.2019.20.6.1613
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of the Urban Women on Pap test: Evidence from Bangladesh

Abstract: Each year, many countries from developed world publishes reports on early cancer detection; which is absolutely absent in most developing countries like Bangladesh.Very limited evidence is found on the role and acceptance of Pap test among the women of Bangladesh in determining cervical cancer. More research and updates are needed relating Pap test in early detection of cervical cancer. Thus the purpose of this study is set to assess the opinions of Bangladeshiurban womentowardsthe Pap test. A questionnaire-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…15 Despite their poor knowledge, participants in the study were willing to receive the HPV vaccine either for themselves or for their daughters. 15 A recent study by Mustari et al 6 Incidence and mortality due to cervical HPV infection was reported to be higher among women aged 50-54 years and 65-74 years, respectively, than among those aged 15-39 years. 9 In light of that report, it is necessary to improve screening rates among the younger females to diagnose cancer at the precursor lesion stage, preferably within 13 years of reaching the last stage of cancer.…”
Section: Cervical Cancer Prevalence In Bangladeshmentioning
confidence: 98%
See 1 more Smart Citation
“…15 Despite their poor knowledge, participants in the study were willing to receive the HPV vaccine either for themselves or for their daughters. 15 A recent study by Mustari et al 6 Incidence and mortality due to cervical HPV infection was reported to be higher among women aged 50-54 years and 65-74 years, respectively, than among those aged 15-39 years. 9 In light of that report, it is necessary to improve screening rates among the younger females to diagnose cancer at the precursor lesion stage, preferably within 13 years of reaching the last stage of cancer.…”
Section: Cervical Cancer Prevalence In Bangladeshmentioning
confidence: 98%
“…4,5 Scaling-up screening strategies based on local needs and resources, vaccination, and improving treatment facilities are the only options for taking immediate action on cervical cancer in LMICs. 3,6,7 In Bangladesh, a low-resource country situated in Southeast Asia (Figure 1) with a female population of approximately 50%, the estimated age-standardized incidence and mortality rates of cervical cancer were approximately 10.6 and 7.1 per 100 000 women, respectively, in 2018. 8 In the same year, 8068 new cases of cervical cancer and 5214 deaths were reported in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, an estimated 8,268 women are diagnosed and 4,971 women die of CCa every year in Bangladesh [6]. Like other less developed countries, the higher rate of mortality due to cervical cancer in Bangladesh has been attributed to several factors such as lack of awareness about its symptoms, risk factors, screening programs, and preventive measures [7]. A study revealed that less than 10% of participants had in-depth knowledge of the causes and possible preventive measures of cervical cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…But in Bangladesh, cervical cancer is being detected at a much later stage because it is too late when women come for diagnosis. An earlier study found that despite Bangladeshi women admitted Pap testing could reduce their risk of cervical cancer, most women neglected screening due to inadequate awareness and lack of facilities [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low healthcare facilities, lack of awareness about its symptoms and risk factors, screening programs, and preventive measures could also play important role. Moreover, social acceptance, social taboos, stigma and ignorance of people eventually makes them delay to take proper treatment and lead them to death [15,18]. Apart from that, other risks are associated with marriage at an early age, multiple sexual partners, prolonged use of oral contraceptive pills, multiple childbirths, immune suppressants, and specific dietary factors (9).…”
Section: Introductionmentioning
confidence: 99%